Metabolic Complications in Cardiac Aging - Sithara, Thomas; Drosatos, Konstantinos (Frontiers in Physiology, 2021)
Aging is a process that can be accompanied by molecular and cellular alterations that compromise cardiac function. Although other metabolic disorders with increased prevalence in aged populations, such as diabetes mellitus, dyslipidemia and hypertension, are associated with cardiovascular complications, aging-related cardiomyopathy has some unique features. Healthy hearts oxidize fatty acids, glucose, lactate, ketone bodies and amino acids for producing energy. Under physiological conditions, cardiac mitochondria use fatty acids and carbohydrate mainly to generate ATP, 70% of which is derived from fatty acid oxidation. However, relative contribution of nutrients in ATP synthesis is altered in the aging heart with glucose oxidation increasing at the expense of fatty acid oxidation. Cardiac aging is also associated with impairment of mitochondrial abundance and function, resulting in accumulation of reactive oxygen species and activation of oxidant signalling that eventually leads to further mitochondrial damage and aggravation of cardiac function. This review summarizes the main components of pathophysiology of cardiac aging, which pertain to cardiac metabolism, mitochondrial function and systemic metabolic changes that affect cardiac function.